Headache : through the centuries - Eadie, Mervyn J. (Oxford University Press, 2012)
Headache: Through the Centuries illuminates the history of headaches with a particular interest in how the disorder has been understood and treated since the earliest recorded accounts, dating from around 4000 BC.Different types of headache were being recognized as early as the 2nd century AD. Over the years, though, the classification of types of headache has changed so that headache patterns described in the past are often difficult to relate to present-day types of headache. Since that time, a great deal of material on the topic has become available, the full gamut of manifestations of the.